2023
DOI: 10.1200/jco.2023.41.17_suppl.lba9000
|View full text |Cite
|
Sign up to set email alerts
|

Pemetrexed and platinum with or without pembrolizumab for tyrosine kinase inhibitor (TKI)-resistant, EGFR-mutant, metastatic nonsquamous NSCLC: Phase 3 KEYNOTE-789 study.

Abstract: LBA9000 Background: EGFR TKIs are standard 1L therapy for metastatic NSCLC with sensitizing EGFR mutations; however, most patients (pts) ultimately experience PD. We report the protocol-specified final analysis (FA) from the randomized, double-blind, phase 3 KEYNOTE-789 study of pemetrexed (pem) and platinum-based chemotherapy (chemo) with or without pembrolizumab (pembro) as subsequent therapy for pts with TKI-resistant, EGFR-mutant, metastatic nonsquamous NSCLC (NCT03515837). Methods: Adults with histologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(30 citation statements)
references
References 0 publications
1
29
0
Order By: Relevance
“…However, pemetrexed based platinum combination has been widely used not only in clinical practice but also in clinical trials. 10,11,22 Finally, the absence of OS benefit is observed in the current analysis, which needs longer follow-up.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…However, pemetrexed based platinum combination has been widely used not only in clinical practice but also in clinical trials. 10,11,22 Finally, the absence of OS benefit is observed in the current analysis, which needs longer follow-up.…”
Section: Discussionmentioning
confidence: 56%
“…Similar trends were observed in CheckMate-722 and KEYNOTE-789, where PFS benefit in PD-L1 ≥50% with an HR of 0.64 (95% CI, 0.36 to 1.15) and OS benefit in PD-L1 ≥1% with an HR of 0.77 (95% CI, 0.58-1.02) were noted, respectively. 10,11 Simultaneously, patients with highly inflamed tumors, as measured by the density of TIL, responded favorably to the ABCP regimen, indicating the essential role of bevacizumab in increasing the sensitivity of atezolizumab by reversing the immunosuppressive tumor microenvironment enriched with TILs in EGFR -mutated NSCLC. 26,27 Further biomarker research is required to identify which patients will benefit from these agents.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…These signals of activity could shed new light on studies testing ICB treatment in populations carrying these resistance markers. For example, the KEYNOTE-789 study ( 37 ) found a modest benefit of ICB plus chemo versus chemo-alone in patients with TKI resistant, EGFR mutant NSCLC; however, this study just failed to attain the predefined efficacy boundaries of P = 0.0117 for PFS and P = 0.0118 for OS. Our results suggest that it is important to study whether this modest benefit of the ICB plus chemo combination in this setting is more pronounced in the context of a high TMB.…”
Section: Discussionmentioning
confidence: 99%